A Study Of Tragedy and its Moral Values in William Shakespeare’s Macbeth: A Structural Analysis - Sigit Cahyo Saputro (LPPM Press, 2012)
This research is aimed to find out the structural elements and its moral values on the play. The analysis covers some structural elements which consist of the theme, the character and characterization, the setting, the plot, the point of view, language and symbolism. The play Macbeth is tragedy and full of conflicts and moral values on the story. And also, it belongs to one of famous plays written by Shakespeare about 1606. The subject of the research is play Macbeth by William Shakespeare and the object of research is the intrinsic elements of the play and the moral values of it. To analyze the structural elements of the play Macbeth, the writer uses the objective approach that anatomizes the work of art itself without relating to external factors such as universe, artists, audience. It focuses on the elements of literary work. The findings of the research show that 1)The theme of the play is a blind ambition. Macbeth is goaded by his more ambitious wife, Lady Macbeth, to be king by evil way. He uses ‘the goal justifies the means’ to obtain it. But it causes the downfall. 2)There are two main characters namely Macbeth and Lady Macbeth and seven minor characters namely King Duncan, Banquo, Three Witches, Macduff, Malcolm, Fleance, Lady Macduff. 3)The setting of time happens in eleventh century ; Meanwhile, the setting of place happens in Scotland and in England, Though, Shakespeare uses the setting of place in beginning of every act. 4)The plot of the play starts from exposition, then it moves to rising action and reaches the climax or turning point. Later, it goes to falling action and the resolution. 5).Shakespeare as author always uses the third person point of view such as He, She, and the name of the character.6)The language that is used is dialog language in the stage and it is old classic English.7)The symbolisms of play which are standing out are blood and darkness. 8)The moral values are divided into positive moral values such as bravery, loyalty, affection, modesty and honesty. and negative moral values such as ambition, atrocity, temptation, vengeance.